DOES INTERNAL MARKETING CONTRIBUTE TO CUSTOMER SATISFACTION? - Juanna, Andi; Bokingo, Agus Hakri (Jurnal Aplikasi Manajemen, 2020)
This study used a quantitative approach to measure the extent to which the implementation of aspects of Internal Marketing can increase job satisfaction of PNM Ulamm Gorontalo employees and their impact on customer satisfaction. The study involved 144 respondents from employee and customer clusters. Data sourced from questionnaires were analyzed using path analysis. The results showed that the internal marketing variable indicator namely service training program had a positive and significant effect on employee job satisfaction; internal marketing variable indicator namely performance incentive has positive and significant effect on employee job satisfaction; internal marketing variable indicators namely vision of service excellence have a positive and significant effect on employee job satisfaction; internal marketing variable indicators namely service training programs do not significantly influence customer satisfaction; indicator of internal marketing variable, performance incentive, does not significantly influence customer satisfaction; internal marketing variable indicator namely vision about service excellence has a significant effect on customer satisfaction; job satisfaction of Ulamm PNM employees has a positive and significant effect on customer satisfaction; Employee job satisfaction in this research model plays a full role as a mediating variable. From the conclusions obtained, the researcher recommends further researchers to be able to broaden the scope of research by involving other banking companies to obtain research results with a broader level of generalization.